PSXIII-1 Does Providing Bedding Change the Latency and Duration of Cattle Lying Behavior During Long-Distance Transport Rest Stops?. (21st September 2022) - Guzman, Paula Olivares; Marti, Sonia; Pearl, David L; Schwartzkopf-Genswein, Karen S; Melendez, Daniela; Haley, Derek B
Abstract: We explored whether straw bedding at rest stations might affect latency and duration of lying down beyond the 8h rest required at rest stops during long distance transport. Animals arriving to commercially operated rest stops (n=75, 6/load, opportunistically selected) were rested in pens (15.5 × 9.5 m) that were either bedded (n=38, straw, 14 cm deep) or non-bedded (n=37). The lying activity of each animal was recorded every 10 min for 8 h. The independent variables recorded included: bedding treatment, mean animal weight/load (kg), and space allowance [k-value = (m 2 /animal) / (BW 2/3 )] in the trailer. Ordinary linear and mixed linear regression models were fitted to assess lying latency and duration, respectively. Bedding affected latency to lie down, but its effect depended on space allowance in the truck: among cattle transported with low space allowance (2.08 - 3.29 m 2 / 300 kg animal), bedded cattle laid down sooner than non-bedded cattle (P< 0.001). Comparing only cattle in bedded pens, cattle laid down sooner when transported with low space allowance (2.08 - 3.29 m 2 / 300 kg animal) compared with medium space allowance (>3.29 – 3.69 m 2 / 300 kg animal; P=0.003). Bedding also affected lying duration, but the effect depended on mean animal weight; as mean animal weight of the load increased so did duration but the effect was greater among bedded animals (P=0.027). In summary, cattle transported at high stocking densities are most likely to benefit from bedding as are heavier animals.